Semantic Classification Of Proverbs Of The Russian And Uzbek Languages (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines the semantic classification of proverbs into thematic groups in the Russian and Uzbek languages. As a result of the study, it was established that the characterized moral qualities, relationships between people, position in society, life experience, attitude to work, behavior, appearance, etc.